Polyolefin resin foam sheet and adhesive tape using same
A polyolefin resin foam sheet with controlled heat shrinkage and shear strength properties addresses the issue of component displacement under high temperatures, ensuring reliable fixing performance for in-vehicle electronic equipment.
Patent Information
- Application Number
- JP2020141258
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-24
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-08-24
AI Technical Summary
Polyolefin resin foams used as foam tapes for fixing in-vehicle electronic equipment face issues with heat resistance, leading to potential displacement of fixed components due to high temperatures, especially when exposed to sunlight.
A polyolefin resin foam sheet with specific heat shrinkage rates and shear strength ratios, combined with controlled thickness, cell diameters, and resin composition, ensuring minimal heat shrinkage and high shear strength at elevated temperatures.
The solution provides a polyolefin resin foam sheet with excellent fixing performance under high temperatures, preventing component displacement and maintaining positional integrity.
Smart Images

Figure 0007616843000001 
Figure 0007616843000002 
Figure 0007616843000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyolefin resin foam sheet and a pressure-sensitive adhesive tape using the same. [Background technology]
[0002] Polyolefin-based resin foams are generally excellent in flexibility, light weight and heat insulation, and are widely used as laminates with skin materials, heat insulation materials, cushioning materials, etc. In addition, polyolefin-based resin foams have excellent flexibility and excellent shock absorption properties, and are therefore used as foam tapes for fixing electronic devices (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-59819 A [Patent Document 2] JP 2018-53224 A [Patent Document 3] JP 2019-65153 A Summary of the Invention [Problem to be solved by the invention]
[0004] When a polyolefin-based resin foam is used for a foam tape for fixing components of an in-vehicle electronic device, there is a concern that the polyolefin-based resin foam may become hot due to the effects of sunlight, etc. In particular, in the case of an in-vehicle electronic device that is retrofitted to a position on the dashboard, the polyolefin-based resin foam may become quite hot. If the polyolefin-based resin foam has low heat resistance, the weight of the component may cause the component fixed to the fixing foam tape to move under high temperatures, resulting in a risk of the component being displaced. Therefore, an object of the present invention is to provide a polyolefin resin foam sheet having excellent fixing performance even at high temperatures, and a pressure-sensitive adhesive tape using the same. [Means for solving the problem]
[0005] As a result of intensive research, the inventors have found that the reason why a component fixed to a fixing foam tape moves due to the weight of the component at high temperatures is due to a decrease in the shear strength of the foam sheet caused by high temperatures. They have also found that the above problem can be solved by using a foam sheet having a heat shrinkage rate within a specified range and a ratio of shear strength at a temperature of 90°C to shear strength at a temperature of 23°C within a specified range, and have completed the present invention. That is, the present invention provides the following [1] to
[12] . [1] When aged at a temperature of 90°C for 1 hour, at least one of the MD shrinkage rate and TD shrinkage rate is 5% or less, and the shear strength (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23 ) is 0.25 or more. [2] The polyolefin resin foam sheet according to the above [1], having a thickness of 1.5 mm or less and a 25% compressive strength of 600 kPa or less. [3] The polyolefin resin foam sheet according to the above [1] or [2], which has a shear strength of 0.15 MPa or more at a temperature of 90°C. [4] The polyolefin resin foam sheet according to any one of the above [1] to [3], wherein at least one of the average cell diameter in MD and the average cell diameter in TD is 250 μm or less. [5] The polyolefin resin foam sheet according to any one of the above [1] to [4], having a degree of crosslinking of 30 to 80 mass %. [6] Apparent density: 0.06 to 0.7 g / cm 3 The polyolefin resin foam sheet according to any one of the above [1] to [5], [7] The polyolefin resin foam sheet according to any one of the above [1] to [6], having a flexural modulus of 160 kPa or less. [8] The polyolefin resin foam sheet according to any one of the above [1] to [7], obtained by foaming a resin composition comprising a resin (A) having a structural unit derived from propylene and a polyethylene resin (B). [9] The polyolefin-based resin foam resin sheet according to the above [8], wherein the resin (A) contains a polypropylene-based resin, an ethylene-propylene random copolymer rubber, and an olefin-based thermoplastic elastomer.
[10] The polyolefin-based resin foam sheet according to the above [9], wherein the total content of the polypropylene-based resin and the ethylene-propylene random copolymer rubber in the resin composition is 50 to 90 parts by mass per 100 parts by mass of the resin component of the resin composition.
[11] The polyolefin resin foam sheet according to the above [9] or
[10] , wherein the content of the olefin thermoplastic elastomer in the resin composition is 2 to 50 parts by mass per 100 parts by mass of the resin component of the resin composition.
[12] A pressure-sensitive adhesive tape comprising the polyolefin resin foam sheet according to any one of the above [1] to
[11] and an adhesive layer provided on at least one surface of the polyolefin resin foam sheet. Effect of the Invention
[0006] According to the present invention, it is possible to provide a polyolefin resin foam sheet having excellent fixing performance at high temperatures, and a pressure-sensitive adhesive tape using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] [Polyolefin resin foam sheet] The polyolefin resin foam sheet of the present invention (hereinafter, may be simply referred to as "foam sheet") has a shrinkage rate in at least one direction, namely, MD or TD, of 5% or less when cured at a temperature of 90°C for 1 hour, and a shear strength (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23) is 0.25 or more. This makes it possible to provide a polyolefin resin foam sheet having excellent fixing performance even at high temperatures. The foam sheet of the present invention will be described in detail below.
[0008] (MD and TD shrinkage rates when cured at 90℃ for 1 hour) When the foam sheet of the present invention is cured at a temperature of 90 ° C. for 1 hour, at least one of the MD shrinkage rate and the TD shrinkage rate is 5% or less. When the foam sheet is cured at a temperature of 90 ° C. for 1 hour, if both the MD shrinkage rate and the TD shrinkage rate are greater than 5%, the foam sheet may not have sufficient heat resistance for use in a high temperature environment inside a vehicle. From the viewpoint of the heat resistance of the foam sheet, at least one of the MD shrinkage rate and the TD shrinkage rate of the foam sheet of the present invention when cured at a temperature of 90 ° C. for 1 hour is preferably 4.0% or less, more preferably 3.5% or less, and even more preferably 3.0% or less. The lower limit of the range of at least one of the MD shrinkage rate and the TD shrinkage rate of the foam sheet of the present invention when cured at a temperature of 90 ° C. for 1 hour is not particularly limited, but is, for example, 0.1% or more. It is more preferable that the foam sheet of the present invention has both the MD shrinkage rate and the TD shrinkage rate when cured at a temperature of 90° C. for 1 hour within the above ranges.
[0009] According to JIS K6767, the dimensional changes of the foam sheet in MD and TD at 90°C are measured, and the heat shrinkage rates (%) in MD and TD are calculated, and these values are regarded as the MD shrinkage rate and the TD shrinkage rate of the foam sheet of the present invention when cured at a temperature of 90°C for 1 hour. In the present invention, "MD" means machine direction, which is the same direction as the extrusion direction of the sheet, etc. "TD" means transverse direction, which is the direction perpendicular to MD and parallel to the surface of the sheet. The MD shrinkage rate and TD shrinkage rate of the foam sheet when cured at a temperature of 90° C. for 1 hour can be adjusted by adjusting the type and content of the resin constituting the foam sheet.
[0010] (Shear strength at 23°C (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23 )) The shear strength (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23 ) is 0.25 or more. 90 / S 23 If the value of S of the foam sheet of the present invention is less than 0.25, when the foam sheet is used as a foam tape for fixing a component of an in-vehicle electronic device, the weight of the component may cause the component fixed by the fixing foam tape to shift from its original position under high temperature. 90 / S 23 The value of S of the foam sheet of the present invention is preferably 0.30 or more, and more preferably 0.35 or more. 90 / S 23 The upper limit of the range of the value is not particularly limited, but is, for example, 1.0 or less. The shear strength of the foam sheet at a temperature of 23° C. and at a temperature of 90° C. can be measured by the method described in the Examples below. In addition, the foam sheet S 90 / S 23 The value of can be adjusted by adjusting the type and content of the resin constituting the foam sheet.
[0011] (shear strength at 90℃) The shear strength of the foam sheet of the present invention at a temperature of 90°C is preferably 0.15 MPa or more. When the foam sheet has a shear strength of 0.15 MPa or more at a temperature of 90°C, when the foam sheet is used as a foam tape for fixing a component of an in-vehicle electronic device, the component fixed to the fixing foam tape can be further prevented from shifting in position due to the weight of the component at high temperatures. From this viewpoint, the shear strength of the foam sheet of the present invention at a temperature of 90°C is more preferably 0.18 MPa or more. The upper limit of the range of the interlaminar strength of the foam sheet of the present invention at a temperature of 90°C is not particularly limited, but is, for example, 2.5 MPa or less. The shear strength of the foam sheet at a temperature of 90° C. can be measured by the method described later in the Examples section. The shear strength of the foam sheet at a temperature of 90° C. can be adjusted by adjusting the type and content of the resin constituting the foam sheet.
[0012] (Thickness) The thickness of the foam sheet of the present invention is preferably 1.5 mm or less. When the thickness of the foam sheet is 1.5 mm or less, the foam sheet can be made to sufficiently follow the curved surface of the member when used in an in-vehicle electronic device having a curved surface. In recent years, in-vehicle displays such as center information displays (CIDs) and head-up displays (HUDs) have become larger and more curved, and a foam tape for fixing a module panel is required to have even higher curved surface conformability. From this perspective, the thickness of the foam sheet is more preferably 1.2 mm or less, even more preferably 0.8 mm or less, even more preferably 0.6 mm or less, and particularly preferably 0.4 mm or less. The lower limit of the thickness range of the foam sheet of the present invention is not particularly limited, but is, for example, 0.03 mm or more.
[0013] (25% compressive strength) The 25% compression strength of the foam sheet of the present invention is, for example, 1000 kPa or less, preferably 600 kPa or less. When the 25% compression strength of the foam sheet is 600 kPa or less, the flexibility of the foam sheet is sufficiently good, and the curved surface followability is improved. From this viewpoint, the 25% compression strength of the foam sheet of the present invention is more preferably 400 kPa or less, further preferably 300 kPa or less, further more preferably 200 kPa or less, and particularly preferably 150 kPa or less. In addition, the 25% compression strength of the foam sheet of the present invention is preferably 30 kPa or more. When the 25% compression strength of the foam sheet is 30 kPa or more, a foam sheet having sufficient mechanical strength for use in electronic devices or in-vehicle electronic devices can be obtained. From this viewpoint, the 25% compression strength of the foam sheet of the present invention is more preferably 40 kPa or more, and further preferably 50 kPa or more. The 25% compression strength of the foam sheet can be measured in accordance with JIS K 7181. The 25% compressive strength of the foam sheet can be adjusted by adjusting the type and content of the resin constituting the foam sheet, the degree of crosslinking of the foam sheet, and the like.
[0014] (Average bubble diameter in MD and TD) At least one of the average bubble diameters in MD and TD in the foam sheet of the present invention is preferably 250 μm or less. When at least one of the average bubble diameters in MD and TD is 250 μm or less, the mechanical strength of the foam sheet is improved and the shear strength is increased. From the viewpoint of the mechanical strength of the foam sheet, at least one of the average bubble diameters in MD and TD is more preferably 230 μm or less, further preferably 200 μm or less, and further more preferably 180 μm or less. The lower limit of the range of at least one of the average bubble diameters in MD and TD in the foam sheet of the present invention is not particularly limited, but is, for example, 40 μm or more. The average bubble diameters in MD and TD in the foam sheet can be measured according to the method described in the examples described below. It is more preferable that both the average cell diameter in MD and the average cell diameter in TD of the foam sheet of the present invention are within the above range. Moreover, the average cell diameters in MD and TD can be adjusted by adjusting the degree of crosslinking of the foam sheet.
[0015] (degree of crosslinking) The crosslinking degree of the foam sheet of the present invention is preferably 30 to 80% by mass. When the crosslinking degree of the foam sheet is 30 to 80% by mass, the average cell diameter in the MD and TD of the foam sheet can be easily adjusted to a desired range. In addition, the shear strength of the foam sheet can be easily increased. From this viewpoint, the crosslinking degree of the foam sheet is more preferably 35 to 75% by mass, further preferably 37 to 72% by mass, and particularly preferably 40 to 70% by mass. The crosslinking degree can be measured according to the method described in the examples below. The crosslinking degree of the foam sheet can be adjusted by adjusting the type and content of the crosslinking assistant, the exposure dose of ionizing radiation, and the like.
[0016] (Apparent density) The apparent density of the foam sheet of the present invention is preferably 0.06 to 0.7 g / cm 3 The apparent density of the foam sheet is 0.06 to 0.7 g / cm 3 From this viewpoint, the apparent density of the foam sheet is more preferably 0.07 to 0.6 g / cm3, and the heat resistance and flexibility of the foam sheet can be improved in a well-balanced manner. 3 and more preferably 0.07 to 0.5 g / cm 3 and particularly preferably 0.1 to 0.3 g / cm 3 It is.
[0017] (Flexural modulus) The flexural modulus of the foam sheet of the present invention is preferably 160 kPa or less. When the flexural modulus of the foam sheet of the present invention is 160 kPa or less, the curved surface conformability of the foam sheet is further improved. From the viewpoint of curved surface conformability, the flexural modulus of the foam sheet is more preferably 100 kPa or less, further preferably 70 kPa or less, and particularly preferably 50 kPa or less. The lower limit of the flexural modulus of the foam sheet is not particularly limited, but is, for example, 5 kPa or more. The flexural modulus can be measured by the method described in the examples below.
[0018] (Resin composition) The foam sheet of the present invention is preferably obtained by foaming a resin composition (hereinafter sometimes referred to as "resin composition (C)") containing a resin (A) (hereinafter sometimes simply referred to as "resin (A)") having a propylene-derived structural unit. Furthermore, the foam sheet of the present invention is more preferably obtained by crosslinking and foaming the resin composition (C). Moreover, it is more preferable that the resin composition (C) further contains a polyethylene resin (B) (hereinafter sometimes simply referred to as "resin (B)") in addition to the resin (A).
[0019] The content of the resin (A) in the resin composition (C) is preferably 60 to 99 parts by mass based on 100 parts by mass of the resin component of the resin composition (C). By using such a resin composition (C), it becomes easier to reduce the heat shrinkage of the foam sheet at a temperature of 90°C, and the S of the foam sheet can be improved. 90 / S 23 From this viewpoint, the content of resin (A) in resin composition (C) is more preferably 70 to 98 parts by mass, and further preferably 80 to 97 parts by mass, per 100 parts by mass of the resin components in resin composition (C).
[0020] The resin (A) preferably contains a polypropylene resin, an ethylene-propylene random copolymer rubber, and an olefin thermoplastic elastomer. By using a resin composition (C) containing such a resin (A), it becomes easier to reduce the heat shrinkage of the foam sheet at a temperature of 90°C, and the S of the foam sheet can be improved. 90 / S 23 It becomes easy to adjust the value of within a predetermined range, and further it becomes easy to improve the curved surface conformability of the foam sheet. From such a viewpoint, the total content of the polypropylene resin, the ethylene-propylene random copolymer rubber, and the olefin thermoplastic elastomer in the resin (A) is preferably 80 to 100 mass%, more preferably 90 to 100 mass%, and further preferably 95 to 100 mass%.
[0021] <Polypropylene resin> By including a polypropylene-based resin in the resin (A), it becomes easier to reduce the heat shrinkage of the foam sheet at a temperature of 90°C, and the S of the foam sheet 90 / S 23 The value of is easily reduced. The polypropylene resin is not particularly limited, and examples thereof include copolymers of propylene and other olefins. The copolymers of propylene and other olefins may be any of block copolymers, random copolymers, and random block copolymers, but are preferably random copolymers of propylene (random polypropylene). By using random polypropylene, the heat resistance of the foam sheet is further improved. In the copolymer of propylene and other olefins, the other olefins copolymerized with propylene include, for example, α-olefins such as ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, and 1-decene, among which ethylene is particularly preferred.That is, as the random copolymer of propylene (random polypropylene), ethylene-propylene random copolymer is more preferred.
[0022] The content of the polypropylene resin in the resin composition (C) is preferably 30 to 90 parts by mass based on 100 parts by mass of the resin component of the resin composition (C). By using such a resin composition (C), it becomes easier to reduce the heat shrinkage of the foam sheet at a temperature of 90°C, and the S of the foam sheet can be improved. 90 / S 23 From this viewpoint, the content of the polypropylene resin in the resin composition (C) is more preferably 35 to 70 parts by mass, further preferably 37 to 65 parts by mass, and particularly preferably 40 to 60 parts by mass, relative to 100 parts by mass of the resin component of the resin composition (C).
[0023] <Ethylene-propylene random copolymer rubber> By including ethylene-propylene random copolymer rubber in resin (A), it becomes easier to reduce the heat shrinkage of the foam sheet at a temperature of 90°C, and the S of the foam sheet 90 / S 23 The ethylene-propylene random copolymer rubber is an amorphous or low-crystalline rubber-like substance in which ethylene and propylene are copolymerized substantially randomly. The ethylene-propylene random copolymer rubber may have other monomer units in addition to the ethylene unit and the propylene unit. Examples of monomers forming the other monomer units include conjugated dienes having 4 to 8 carbon atoms such as 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene, non-conjugated dienes having 5 to 15 carbon atoms such as dicyclopentadiene, 5-ethylidene-2-norbornene, 1,4-hexadiene, 1,5-dicyclooctadiene, 7-methyl-1,6-octadiene, and 5-vinyl-2-norbornene, vinyl ester compounds such as vinyl acetate, unsaturated carboxylic acid esters such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, and ethyl methacrylate, and unsaturated carboxylic acids such as acrylic acid and methacrylic acid. These monomers may be used alone or in combination of two or more. Among these, non-conjugated dienes having 5 to 15 carbon atoms are preferred, and from the viewpoint of availability, 5-ethylidene-2-norbornene, 1,4-hexadiene, and dicyclopentadiene (DCPD) are more preferred, with 5-ethylidene-2-norbornene being even more preferred.
[0024] The ethylene unit content of the ethylene-propylene random copolymer rubber is usually 30 to 85 mass%, preferably 40 to 80 mass%, more preferably 45 to 75 mass%, the propylene unit content is usually 10 to 60 mass%, preferably 15 to 50 mass%, and the content of other monomer units such as non-conjugated dienes is usually 0 to 20 mass%, preferably 0 to 10 mass%.
[0025] The ethylene-propylene random copolymer rubber is preferably ethylene-propylene copolymer rubber (EPR) and ethylene-propylene-diene copolymer rubber (EPDM), and more preferably EPDM. Incidentally, examples of EPDM include ethylene-propylene-5-ethylidene-2-norbornene copolymer rubber, ethylene-propylene-1,4-hexadiene copolymer rubber, and ethylene-propylene-dicyclopentadiene copolymer rubber, and among these, ethylene-propylene-5-ethylidene-2-norbornene copolymer rubber is preferred. These ethylene-propylene random copolymer rubbers can be used alone or in combination of two or more kinds.
[0026] The content of the ethylene-propylene random copolymer rubber in the resin composition (C) is preferably 2 to 40 parts by mass relative to 100 parts by mass of the resin component of the resin composition (C). By using such a resin composition (C), the heat resistance of the foam sheet can be improved, and the curved surface conformability of the foam sheet can be improved. From this viewpoint, the content of the ethylene-propylene random copolymer rubber in the resin composition (C) is more preferably 10 to 35 parts by mass, further preferably 15 to 30 parts by mass, and particularly preferably 20 to 25 parts by mass relative to 100 parts by mass of the resin component of the resin composition (C).
[0027] The total content of the polypropylene resin and the ethylene-propylene random copolymer rubber in the resin composition (C) is preferably 50 to 90 parts by mass relative to 100 parts by mass of the resin component of the resin composition (C). By using such a resin composition (C), the heat resistance of the foam sheet can be further improved, and the curved surface conformability of the foam sheet can be further improved. From this viewpoint, the total content of the polypropylene resin and the ethylene-propylene random copolymer rubber in the resin composition (C) is more preferably 55 to 85 parts by mass, further preferably 60 to 80 parts by mass, and particularly preferably 65 to 80 parts by mass relative to 100 parts by mass of the resin component of the resin composition (C).
[0028] <Olefin-based thermoplastic elastomer (TPO)> Olefin-based thermoplastic elastomers (TPOs) generally have polyolefin-based resins such as polyethylene-based resins and polypropylene-based resins as hard segments, and polyolefin-based rubbers such as EPR and EPDM as soft segments. Any of blend, dynamic crosslinking, and polymerization types of TPOs can be used. TPOs in which fine particles of polyolefin-based rubber are dispersed in a polyolefin-based resin matrix are preferred. In the TPO used in the foam sheet of the present invention, at least one of the polyolefin compounds of the polyolefin resin and the polyolefin rubber has a propylene-derived structural unit. When the resin (A) contains such a TPO, the heat resistance of the foam sheet can be improved, and the flexibility of the foam sheet can be improved. In the TPO used in the foam sheet of the present invention, it is more preferable that both the polyolefin resin and the polyolefin rubber have a propylene-derived structural unit. In addition, it is more preferable that the polyolefin resin is a polypropylene resin. An example of a commercially available TPO product that can be used for the foam sheet of the present invention is an olefin-based thermoplastic elastomer manufactured by Prime Polymer Co., Ltd. (product name: Prime TPO, model number: E-2710, MFR: 2.8 g / 10 min).
[0029] From the viewpoint of improving the heat resistance and curved surface conformability of the foam sheet, the content of TPO in the resin component of resin composition (C) is preferably 2 to 50 parts by mass, more preferably 5 to 45 parts by mass, even more preferably 10 to 40 parts by mass, and particularly preferably 15 to 35 parts by mass, per 100 parts by mass of the resin component.
[0030] When the resin (A) contains a polypropylene-based resin, the heat shrinkage of the foam sheet at a temperature of 90°C is easily reduced, and the S of the foam sheet is easily reduced. 90 / S 23The value of can be easily increased. Furthermore, when the resin (A) further contains an ethylene-propylene random copolymer rubber and an olefin-based thermoplastic elastomer (TPO), the compatibility between the polypropylene-based resin and the ethylene-propylene random copolymer rubber is improved, and the curved surface conformability of the foam sheet can be improved. From this viewpoint, it is preferable that the resin (A) contains a polypropylene-based resin, an ethylene-propylene random copolymer rubber, and an olefin-based thermoplastic elastomer (TPO).
[0031] <Polyethylene resin (B)> The resin composition (C) preferably further contains a polyethylene resin (B). This improves the flexibility of the foam sheet and improves the compatibility between the resin (A) and the additives described below. Examples of the polyethylene resin include low-density polyethylene resin, medium-density polyethylene resin, high-density polyethylene resin, and linear low-density polyethylene resin. Among these, linear low-density polyethylene resin (LLDPE) is preferred.
[0032] Linear low-density polyethylene resin has a density of 0.910 g / cm 3 More than 0.950g / cm 3 and preferably has a density of 0.910 to 0.940 g / cm 3 The foam contains a linear low-density polyethylene resin having a low density, which tends to improve the processability when the resin composition is processed into a foam and the moldability when the foam is molded into a molded article. The density of the resin is measured in accordance with JIS K7112.
[0033] Linear low density polyethylene is usually a copolymer of ethylene and a small amount of α-olefin, with ethylene being the main component (80% by mass or more of the total monomers, preferably 90% by mass or more, more preferably 95% by mass or more). Here, the α-olefin may have 3 to 12 carbon atoms, preferably 4 to 10 carbon atoms, and specific examples thereof include 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, and 1-octene. In the copolymer, these α-olefins may be used alone or in combination of two or more kinds. Moreover, these polyethylene resins may be used alone or in combination of two or more kinds.
[0034] From the viewpoint of improving the flexibility of the foam sheet and the compatibility between the resin (A) and the additives, the content of the polyethylene resin (B) in the resin composition (C) is preferably 1 to 40 parts by mass, more preferably 2 to 30 parts by mass, and even more preferably 3 to 20 parts by mass, per 100 parts by mass of the resin component.
[0035] <Other resin components> As long as the object of the present invention is not impaired, the resin composition (C) may contain a resin component other than the polypropylene resin, the ethylene-propylene random copolymer rubber, the olefin thermoplastic elastomer, and the polyethylene resin. Examples of such a resin component include an ethylene-vinyl acetate copolymer, an ethylene-acrylic acid copolymer, an ethylene-(meth)alkyl acrylate copolymer, or a modified copolymer obtained by copolymerizing these with maleic anhydride.
[0036] From the viewpoint of improving the heat resistance and flexibility of the foam sheet, the total content of the resin (A) having a structural unit derived from propylene and the polyethylene resin (B) in the resin composition (C) is preferably 70 to 99 mass%, more preferably 80 to 98 mass%.
[0037] <Additives> The resin composition (C) generally contains a crosslinking aid and a foaming agent as additives other than the olefin resin. The resin composition (C) may further contain a decomposition temperature regulator. Furthermore, the resin composition (C) preferably contains an antioxidant.
[0038] Crosslinking agent As the crosslinking aid, a multifunctional monomer can be used. For example, trifunctional (meth)acrylate compounds such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate, compounds having three functional groups in one molecule such as trimellitic acid triallyl ester, 1,2,4-benzene tricarboxylic acid triallyl ester, and triallyl isocyanurate, bifunctional (meth)acrylate compounds such as 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, and neopentyl glycol dimethacrylate, compounds having two functional groups in one molecule such as divinylbenzene, diallyl phthalate, diallyl terephthalate, diallyl isophthalate, ethylvinylbenzene, lauryl methacrylate, and stearyl methacrylate can be mentioned. Among these, trifunctional (meth)acrylate compounds are more preferable, and trimethylolpropane trimethacrylate is even more preferable. The crosslinking assistants may be used alone or in combination of two or more. By adding the crosslinking aid to the resin composition (C), it becomes possible to crosslink the resin composition (C) with a small amount of ionizing radiation, and therefore it is possible to suppress the scission and deterioration of each resin molecule that accompanies the irradiation of ionizing radiation. The content of the crosslinking aid is preferably 0.2 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the resin component, from the viewpoint of ease of adjustment and control of the degree of crosslinking when foaming the resin composition (C).
[0039] Foaming Agent Methods for foaming the resin composition (C) include a chemical foaming method and a physical foaming method. The chemical foaming method is a method in which bubbles are formed by gas generated by thermal decomposition of a compound added to the resin composition (C), and the physical foaming method is a method in which a low-boiling point liquid (foaming agent) is impregnated into the resin composition (C) and then the foaming agent is volatilized to form cells. The foaming method is not particularly limited, but from the viewpoint of obtaining a uniform closed-cell foam sheet, the chemical foaming method is preferred. As the foaming agent, a thermal decomposition type foaming agent is preferably used, and for example, an organic or inorganic chemical foaming agent having a decomposition temperature of about 160 to 270° C. can be used. Examples of organic blowing agents include azo compounds such as azodicarbonamide, metal azodicarboxylates (e.g., barium azodicarboxylate), and azobisisobutyronitrile; nitroso compounds such as N,N'-dinitrosopentamethylenetetramine; hydrazine derivatives such as hydrazodicarbonamide, 4,4'-oxybis(benzenesulfonylhydrazide), and toluenesulfonylhydrazide; and semicarbazide compounds such as toluenesulfonylsemicarbazide.
[0040] Examples of inorganic foaming agents include ammonium carbonate, sodium carbonate, ammonium hydrogen carbonate, sodium hydrogen carbonate, ammonium nitrite, sodium borohydride, and anhydrous monosodium citrate. Among these, from the viewpoint of obtaining fine bubbles and from the viewpoints of economy and safety, azo compounds and nitroso compounds are preferred, azodicarbonamide, azobisisobutyronitrile and N,N'-dinitrosopentamethylenetetramine are more preferred, and azodicarbonamide is particularly preferred. The foaming agents may be used alone or in combination of two or more kinds. The amount of the thermally decomposable foaming agent added is preferably 1 to 25 parts by mass, more preferably 1.3 to 15 parts by mass, and even more preferably 1.5 to 10 parts by mass, per 100 parts by mass of the resin component, from the viewpoint of adequate foaming without bursting the cells of the foam sheet.
[0041] Decomposition temperature regulator Examples of the decomposition temperature regulator include basic magnesium salt, zinc oxide, zinc stearate, and urea. These decomposition temperature regulators can be used alone or in combination of two or more. Among these decomposition temperature regulators, basic magnesium salts are preferred. Furthermore, the basic magnesium preferred as the decomposition temperature regulator is at least one magnesium compound selected from the group consisting of magnesium oxide and magnesium hydroxide. The resin composition (C) may contain only one of magnesium oxide and magnesium hydroxide, or may contain both. However, it is preferred that the resin composition (C) contains both magnesium oxide and magnesium hydroxide. By blending a decomposition temperature foaming agent in the resin composition (C), the decomposition temperature of the thermal decomposition type foaming agent can be adjusted, and the cell diameter of the foam sheet can be adjusted with even higher accuracy. When the foaming agent, especially azodicarbonamide, is decomposed by heating, a part of it becomes a sublimate, and fogging occurs. However, by including basic magnesium in the resin composition (C), the occurrence of fogging caused by such sublimates is prevented. Therefore, in the present invention, when azodicarbonamide is used as the foaming agent, it is preferable that the resin composition (C) includes basic magnesium.
[0042] The content of the decomposition temperature regulator in the resin composition (C) is preferably 0.03 to 3.0 parts by mass, more preferably 0.04 to 2.5 parts by mass, and even more preferably 0.05 to 2.0 parts by mass, based on 100 parts by mass of the resin component.
[0043] Antioxidants Examples of the antioxidant include phenol-based antioxidants, sulfur-based antioxidants, phosphorus-based antioxidants, amine-based antioxidants, etc. Among these, phenol-based antioxidants and sulfur-based antioxidants are preferred, and it is more preferred to use a phenol-based antioxidant and a sulfur-based antioxidant in combination. Examples of phenol-based antioxidants include 2,6-di-tert-butyl-p-cresol, n-octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenylacrylate, and tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane. Examples of the sulfur-based antioxidants include dilauryl thiodipropionate, dimyristyl thiodipropionate, distearyl thiodipropionate, and pentaerythrityl tetrakis(3-lauryl thiopropionate). Of these phenolic antioxidants, 2,6-di-tert-butyl-p-cresol is preferred, and of these sulfur-based antioxidants, dilauryl thiodipropionate is preferred. These antioxidants may be used alone or in combination of two or more kinds. The content of the antioxidant is preferably from 0.1 to 10 parts by mass, and more preferably from 0.2 to 5 parts by mass, based on 100 parts by mass of the resin component. Furthermore, the resin composition (C) may contain additives other than those mentioned above, such as a flame retardant, a metal damage inhibitor, an antistatic agent, a stabilizer, a filler, and a pigment, if necessary.
[0044] The foam sheet of the present invention has excellent heat resistance and is therefore suitable for use in electronic devices, particularly in in-vehicle electronic devices. Furthermore, the foam sheet of the present invention preferably has excellent curved surface conformability and is therefore also suitable for use in in-vehicle image display devices such as center information displays (CIDs) and head-up displays (HUDs).
[0045] <Method of manufacturing foam sheet> The foam sheet of the present invention can be produced, for example, by melt-kneading the resin composition (C), forming it into a desired shape, and then irradiating it with ionizing radiation to heat and foam the resin composition (C). Specifically, a production method including the following steps 1 to 3 is more preferable. Step 1: A step of melt-kneading each component constituting the resin composition (C) and then obtaining a sheet-shaped resin composition (C) Step 2: A step of crosslinking the resin composition (C) obtained in step 1 by irradiating it with ionizing radiation. Step 3: A step of heating the resin composition (C) crosslinked in step 2 to a temperature equal to or higher than the decomposition temperature of the thermally decomposable foaming agent to foam the composition, thereby obtaining a foam sheet.
[0046] In step 1, each component constituting the resin composition (C) is supplied to a kneading device and melt-kneaded at a temperature lower than the decomposition temperature of the thermally decomposable foaming agent, and then the melt-kneaded resin composition (C) is formed into a sheet, preferably using the kneading device used for melt-kneading. Examples of the kneading device used here include general-purpose kneading devices such as an injection molding machine, an extruder (such as a single-screw extruder or a twin-screw extruder), a Banbury mixer, and a roll. Of these, an injection molding machine or an extruder is preferred, and the use of an injection molding machine allows for production with good productivity. The resin temperature inside the injection molding machine or extruder is preferably 120 to 220°C, more preferably 140 to 200°C, and further preferably 150 to 195°C.
[0047] In step 2, the resin composition (C) formed into a sheet is irradiated with ionizing radiation. Examples of ionizing radiation include electron beams, α rays, β rays, γ rays, X-rays, etc. Among these, electron beams are preferred from the viewpoints of productivity and uniform irradiation. The resin composition (C) formed into a sheet may be irradiated with ionizing radiation on only one side or on both sides. The acceleration voltage of the ionizing radiation depends on the thickness of the foamable resin composition to be irradiated, but when the thickness is, for example, 0.05 to 3 mm, it is preferably 400 to 1200 kV, more preferably 500 to 1100 kV, and even more preferably 600 to 1000 kV. The exposure dose of ionizing radiation may be any amount that can obtain a desired degree of crosslinking without causing surface roughness or cracking, taking into consideration the thickness of the foamable resin composition to be irradiated, and is usually preferably 0.1 to 10 Mrad, more preferably 0.2 to 5 Mrad, and still more preferably 0.3 to 3 Mrad.
[0048] In step 3, after the resin composition (C) is crosslinked by irradiation with ionizing radiation as described above, the resin composition (C) is heated to a temperature equal to or higher than the decomposition temperature of the foaming agent to be foamed, thereby obtaining a foam sheet. After foaming the resin composition (C) or while foaming the resin composition (C), the resin composition (C) may be stretched in either or both of the MD and CD directions. The temperature at which the resin composition (C) is heated and foamed depends on the decomposition temperature of the thermally decomposable foaming agent used as the foaming agent, but is usually 140 to 300°C, preferably 150 to 280°C, and more preferably 160 to 260°C. The foam sheet of the present invention preferably has a closed cell structure, but may have a closed cell structure containing open cells.
[0049] [Adhesive tape] The adhesive tape of the present invention is an adhesive tape using the above-mentioned foam sheet of the present invention as a substrate, and specifically comprises the foam sheet of the present invention and an adhesive layer provided on at least one surface of the foam sheet of the present invention. The pressure-sensitive adhesive tape of the present invention preferably has pressure-sensitive adhesive layers provided on both sides of a foam sheet, that is, the pressure-sensitive adhesive tape of the present invention is preferably a double-sided tape. In addition, since the pressure-sensitive adhesive tape of the present invention can seal even a gap having a curved surface, it can be used to more reliably prevent the intrusion of dust, moisture, etc. from the outside to the inside of an electronic device having a curved surface. Therefore, the pressure-sensitive adhesive tape of the present invention can be suitably used as a sealant for electronic devices, particularly as a sealant for in-vehicle electronic devices, and more suitably used as a sealant for in-vehicle electronic devices having a curved surface.
[0050] The adhesive layer is a layer having adhesiveness at least on the surface opposite to the foam sheet side. Examples of the adhesive layer include an adhesive layer made of an adhesive alone, a double-sided tape having an adhesive layer on both sides of a substrate, etc. From the viewpoint of making the adhesive tape thinner, the adhesive layer is preferred. The thickness of the adhesive layer constituting the adhesive tape is preferably from 5 to 200 μm, more preferably from 7 to 150 μm, and even more preferably from 10 to 100 μm.
[0051] The adhesive constituting the adhesive portion of the adhesive layer is not particularly limited, and examples thereof include acrylic adhesives, urethane adhesives, rubber adhesives, silicone adhesives, and the like. Examples of the method for laminating the adhesive layer on the foam sheet include a method for transferring the adhesive applied to a release paper to the foam sheet, and a method for applying the adhesive to at least one surface of the foam sheet using a coating machine such as a coater. Other methods for laminating the adhesive layer on the foam sheet include a method for spraying and applying the adhesive to at least one surface of the foam sheet using a spray, and a method for applying the adhesive to one surface of the foam sheet using a brush. On the other hand, examples of the method for laminating the double-sided tape on the foam sheet include a method for attaching the double-sided tape to the foam sheet.
[0052] The pressure-sensitive adhesive tape of the present invention uses a foam sheet having excellent heat resistance as a substrate, and is therefore suitable for use in electronic devices, particularly in on-vehicle electronic devices. Furthermore, since the foam sheet preferably has excellent curved surface conformability, the pressure-sensitive adhesive tape of the present invention is also suitable for use in on-vehicle image display devices such as center information displays (CIDs) and head-up displays (HUDs) by using the foam sheet as a substrate. EXAMPLES
[0053] The present invention will be described below with reference to examples, but the present invention is not limited to these examples in any way. The methods for measuring the various physical properties and the methods for evaluating the foam sheet are as follows.
[0054] (1) Degree of crosslinking A test piece of about 100 mg was taken from the foam sheet, and the mass A (mg) of the test piece was precisely weighed. Next, this test piece was immersed in 30 cm of xylene at 120 °C. 3 After immersion for 24 hours, the insoluble matter on the wire mesh was collected by filtration through a 200-mesh wire mesh and dried in a vacuum, and the mass B (mg) of the insoluble matter was precisely weighed. The degree of crosslinking (mass%) was calculated from the obtained value using the following formula. Crosslinking degree (mass%) = 100×(B / A) (2) Density of foam sheet The density (apparent density) of the foam sheet was measured in accordance with JIS K7222. (3) Thickness of the foam sheet The thickness of the foam sheet was measured using a dial gauge. (4) Flexural modulus The foam sheet was cut to a width of 25 mm and a length of 30 mm, and the sheets were stacked to a thickness of 30 mm. Other test methods were based on JIS 7171, 7221-2, and the flexural modulus was measured using a Tensilon (manufactured by ORIENTEC, product name: RTC-1310A). The calculation method was to plot the elongation measured by the above method (mm) on the horizontal axis and the load (N) on the vertical axis, and the slope value when the slope of the plot within the elongation range of 0.5 mm to 5 mm was maximum was taken as the flexural modulus. (5) Average bubble diameter The foam sheet was cut into 50 mm squares, immersed in liquid nitrogen for 1 minute, cut along the MD and TD, and photographed at 200x magnification using a digital microscope (Keyence Corporation, product name VHX-900). For the foam sheet in the photographed image, the bubble diameters in the MD and TD were measured for all bubbles present on the cut surface of 2 mm length in each of the MD and TD, and this operation was repeated five times. The average value of the bubble diameters in the MD and TD (average bubble diameter) was then calculated. (6) Heat shrinkage In accordance with JIS K6767, the dimensional changes of the foam sheet in MD and TD at 90°C were measured, and the heat shrinkage rate (%) in MD at 90°C and the heat shrinkage rate (%) in TD at 90°C were calculated. (7) 25% compressive strength The 25% compressive strength was measured in accordance with JIS K6767. (8) Shear strength at 23°C and 90°C The adhesive was applied to a 30 mm square area of the foam sheet. Immediately afterwards, a wooden jig A with a short side of 30 mm and a long side of 100 mm was placed so as to overlap the adhesive-applied area, and the foam sheet and jig A were pressed together. After that, the foam sheet was cut to the size of the jig A. Next, adhesive was applied to the surface of the cut foam sheet to which jig A was not attached, and immediately thereafter, a wooden jig B was placed on top of the foam sheet, and the foam sheet and jig B were pressure-bonded together. This was left at room temperature for 24 hours to cure the adhesive, and a sample for measuring shear strength was obtained. Next, a 2.5 kN load cell was installed in a testing machine ("Tensilon Universal Material Testing Machine" manufactured by A & D Co., Ltd.) equipped with a thermostatic bath so that tests could be performed in the thermostatic bath. Then, a sample for measuring shear strength was attached so that the sheet surface of the foam sheet was parallel to the tensile direction. After the temperature of the thermostatic bath was set to 23°C, the sample for measuring interlaminar strength was left until the temperature of the sample for measuring interlaminar strength reached 23°C. Then, under the condition of a temperature of 23°C, one side of the jig was pulled vertically upward at a speed of 100 mm / min to cause delamination of the foam sheet. The load at this time was measured, and the maximum value was taken as the shear strength. The same operation was repeated three times, and the average value was taken as the shear strength (S 23 ) was decided. In addition, the shear strength (S) at 90°C was measured in the same manner as the shear strength at 23°C, except that the temperature of the thermostatic bath was changed from 23°C to 90°C. 90 ) was measured. (9) Heat resistance shear evaluation The inventors have determined the ratio (S 90 / S 23It has been found that if the value of ) is 0.25 or more, by using the foam sheet as a fixing foam tape, the movement of the component fixed to the fixing foam tape due to the weight of the component at high temperatures can be significantly suppressed. Therefore, using the above-mentioned measurement results of the shear strength at 23°C and 90°C, the heat resistance shear evaluation of the foam sheet was performed according to the following criteria. ○: Shear strength at 23℃ (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23 ) was 0.25 or higher. ×: Shear strength at 23°C (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23 ) was less than 0.25. (10) Ability to follow 90° curved surfaces The foam sheet was provided with an adhesive layer, attached to an acrylic plate with a radius of curvature R = 0.095 (m), and left to stand at 90°C for 24 hours. The attached portion was then checked, and curved surface conformability was evaluated based on the presence or absence of tape lifting and wrinkles. When there was no tape lifting or wrinkles, it was evaluated as "○", and when at least one of tape lifting and wrinkles occurred, it was evaluated as "×". Note that an acrylic adhesive (manufactured by Sekisui Chemical Co., Ltd., model number: #5782) was used for the adhesive layer.
[0055] (Preparation of foam sheets of Examples 1 to 11, Comparative Examples 1 and 2, and the sheet of Comparative Example 3) <Example 1> 40 parts by mass of random PP, 25 parts by mass of EPDM, 30 parts by mass of TPO, 5 parts by mass of LLDPE, 1.5 parts by mass of a thermally decomposable foaming agent, 1 part by mass of a decomposition temperature regulator, 0.5 parts by mass of an antioxidant, and 3 parts by mass of a crosslinking aid were put into a single screw extruder. Then, the above-mentioned raw materials were melt-kneaded and extruded at a resin temperature of 180°C to obtain a sheet-shaped resin composition. Both sides of this sheet-shaped resin composition were irradiated with an electron beam with an irradiation dose of 1.8 Mrad to crosslink the sheet-shaped resin composition. Thereafter, the crosslinked sheet-shaped resin composition was stretched in MD and TD and heated at 250°C for 5 minutes in a hot air oven, and the sheet-shaped resin composition was foamed by the heating to obtain a foam sheet of Example 1.
[0056] <Example 2> The amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 2.6 parts by mass, the electron beam irradiation dose was changed from 1.8 Mrad to 2.2 Mrad, and the thickness of the sheet-shaped resin composition was changed. Except for these, a foam sheet of Example 2 was obtained in the same manner as the foam sheet of Example 1.
[0057] <Example 3> The amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 4.5 parts by mass, the amount of the crosslinking assistant was changed from 3 parts by mass to 4 parts by mass, the electron beam irradiation dose was changed from 1.8 Mrad to 1.3 Mrad, and the thickness of the sheet-shaped resin composition was changed. A foam sheet of Example 3 was obtained by the same production method as that of the foam sheet of Example 1.
[0058] <Example 4> The amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 4.5 parts by mass, the electron beam irradiation dose was changed from 1.8 Mrad to 2.2 Mrad, and the thickness of the sheet-shaped resin composition was changed. Except for these, a foam sheet of Example 4 was obtained in the same manner as the foam sheet of Example 1.
[0059] <Example 5> The amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 8 parts by mass, the electron beam irradiation dose was changed from 1.8 Mrad to 2.2 Mrad, and the thickness of the sheet-shaped resin composition was changed. A foam sheet of Example 5 was obtained in the same manner as the foam sheet of Example 1.
[0060] <Example 6> The amount of random PP was changed from 40 parts by mass to 50 parts by mass, the amount of EPDM was changed from 25 parts by mass to 20 parts by mass, and the amount of TPO was changed from 30 parts by mass to 35 parts by mass. In addition, the amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 3.8 parts by mass, the amount of the decomposition temperature regulator was changed from 1 part by mass to 2 parts by mass, and the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 2.5 Mrad, and the thickness of the sheet-shaped resin composition was changed. Otherwise, the foam sheet of Example 6 was obtained by the same production method as that of the foam sheet of Example 1.
[0061] <Example 7> The amount of random PP was changed from 40 parts by mass to 60 parts by mass, the amount of EPDM was changed from 25 parts by mass to 20 parts by mass, and the amount of TPO was changed from 30 parts by mass to 15 parts by mass. In addition, the amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 8 parts by mass, the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass, and the amount of the crosslinking assistant was changed from 3 parts by mass to 3.5 parts by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 2.5 Mrad, and the thickness of the sheet-shaped resin composition was changed. Otherwise, the foam sheet of Example 7 was obtained by the same production method as that of the foam sheet of Example 1.
[0062] <Example 8> The amount of EPDM was changed from 25 parts by mass to 20 parts by mass, and the amount of TPO was changed from 30 parts by mass to 35 parts by mass. The amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 5 parts by mass, the amount of the decomposition temperature regulator was changed from 1 part by mass to 1.5 parts by mass, the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass, and the amount of the crosslinking auxiliary was changed from 3 parts by mass to 4 parts by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 2.8 Mrad, and the thickness of the sheet-shaped resin composition was changed. A foam sheet of Example 8 was obtained by the same production method as that of the foam sheet of Example 1.
[0063] <Example 9> The amount of EPDM was changed from 25 parts by mass to 20 parts by mass, and the amount of TPO was changed from 30 parts by mass to 35 parts by mass. The amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 6 parts by mass, the amount of the decomposition temperature regulator was changed from 1 part by mass to 1.5 parts by mass, and the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 2.8 Mrad, and the thickness of the sheet-shaped resin composition was changed. A foam sheet of Example 9 was obtained by the same production method as that of the foam sheet of Example 1.
[0064] <Example 10> The amount of random PP was changed from 40 parts by mass to 60 parts by mass, the amount of EPDM was changed from 25 parts by mass to 20 parts by mass, and the amount of TPO was changed from 30 parts by mass to 15 parts by mass. In addition, the amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 8 parts by mass, the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass, and the amount of the crosslinking assistant was changed from 3 parts by mass to 3.5 parts by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 2.2 Mrad, and the thickness of the sheet-shaped resin composition was changed. Otherwise, the foam sheet of Example 10 was obtained by the same production method as that of the foam sheet of Example 1.
[0065] <Example 11> The amount of random PP was changed from 40 parts by mass to 80 parts by mass, the amount of EPDM was changed from 25 parts by mass to 0 parts by mass, the amount of TPO was changed from 30 parts by mass to 0 parts by mass, and the amount of LLDPE was changed from 5 parts by mass to 20 parts by mass. In addition, the amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 3 parts by mass, the amount of the decomposition temperature regulator was changed from 1 part by mass to 3.7 parts by mass, the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass, and the amount of the crosslinking assistant was changed from 3 parts by mass to 0.5 parts by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 2.2 Mrad, and the thickness of the sheet-shaped resin composition was changed. Otherwise, the foam sheet of Example 11 was obtained by the same production method as that of the foam sheet of Example 1.
[0066] <Comparative Example 1> The amount of EPDM was changed from 25 parts by mass to 20 parts by mass, and the amount of TPO was changed from 30 parts by mass to 35 parts by mass. The amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 3 parts by mass, the amount of the decomposition temperature regulator was changed from 1 part by mass to 3.5 parts by mass, the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass, and the amount of the crosslinking auxiliary was changed from 3 parts by mass to 0.5 parts by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 1.2 Mrad, and the thickness of the sheet-shaped resin composition was changed. A foam sheet of Comparative Example 1 was obtained by the same production method as that of the foam sheet of Example 1.
[0067] <Comparative Example 2> The amount of random PP was changed from 40 parts by mass to 0 parts by mass, the amount of EPDM was changed from 25 parts by mass to 0 parts by mass, the amount of TPO was changed from 30 parts by mass to 0 parts by mass, and the amount of LLDPE was changed from 5 parts by mass to 100 parts by mass. In addition, the amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 2.6 parts by mass, the amount of the decomposition temperature regulator was changed from 1 part by mass to 1.5 parts by mass, the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass, and the amount of the crosslinking assistant was changed from 3 parts by mass to 0 parts by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 2 Mrad, and the thickness of the sheet-shaped resin composition was changed. A foam sheet of Comparative Example 2 was obtained by the same production method as that of the foam sheet of Example 1.
[0068] <Comparative Example 3> The amount of random PP was changed from 40 parts by mass to 0 parts by mass, the amount of EPDM was changed from 25 parts by mass to 20 parts by mass, the amount of TPO was changed from 30 parts by mass to 35 parts by mass, and the amount of LLDPE was changed from 5 parts by mass to 45 parts by mass. In addition, the amount of the thermally decomposable foaming agent was changed from 1.5 parts by mass to 0 parts by mass, the amount of the decomposition temperature regulator was changed from 1 part by mass to 3.7 parts by mass, the amount of the antioxidant was changed from 0.5 parts by mass to 1 part by mass, and the amount of the crosslinking assistant was changed from 3 parts by mass to 0.5 parts by mass. Furthermore, the irradiation dose of the electron beam was changed from 1.8 Mrad to 1.3 Mrad, and the thickness of the sheet-shaped resin composition was changed. Otherwise, a sheet of Comparative Example 3 was obtained by the same production method as the foam sheet of Example 1.
[0069] The physical properties and evaluation results of the foam sheets of Examples 1 to 11, Comparative Examples 1 and 2, and the sheet of Comparative Example 3 are shown in Tables 1 to 3.
[0070] [Table 1]
[0071] [Table 2]
[0072] [Table 3]
[0073] Details of the resin components and additives shown in Tables 1 to 3 are as follows. Random PP: Ethylene-propylene random copolymer, manufactured by Japan Polypropylene Corporation, product name: Novatec FY6C, MFR: 2.4g / 10min, ethylene content: 3% by mass EPDM: Ethylene-propylene-diene copolymer, manufactured by JSR Corporation, Product name: JSR EP51, Mooney viscosity (ML 1+4 , 100 ° C) = 23, ethylene content: 67 mass%, ENB (ethylidene norbornene) content: 5.8 mass% TPO: Olefin-based thermoplastic elastomer, manufactured by Prime Polymer Co., Ltd., Product name: Prime TPO, Model number: E-2710, MFR: 2.8g / 10min, LLDPE: Linear low-density polyethylene, manufactured by Dow Chemical Company, product name: 2036P, MFR: 2.5g / 10min Thermal decomposition type blowing agent: Azodicarbonamide Decomposition temperature regulator: Magnesium oxide, magnesium hydroxide Antioxidants: 2,6-di-tert-butyl-p-cresol, dilauryl thiodipropionate Crosslinking agent: Trimethylolpropane trimethacrylate, manufactured by Tokyo Chemical Industry Co., Ltd.
[0074] In the foam sheets of Examples 1 to 11, when the foam sheets were cured at a temperature of 90° C. for 1 hour, at least one of the MD shrinkage rate and the TD shrinkage rate was 5% or less, and the shear strength (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23) was 0.25 or more. This shows that the foam sheets of Examples 1 to 11 have excellent fixing performance at high temperatures. However, since the 25% compressive strength of the foam sheet of Example 11 was greater than 600 kPa, the evaluation result of the foam sheet of Example 11 in terms of conformability to a curved surface at 90°C was poor. On the other hand, the foam sheets of Comparative Examples 1 and 2 had a shear strength (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23 ) was less than 0.25. In addition, in the sheet of Comparative Example 3, both the MD shrinkage rate and the TD shrinkage rate when the sheet was aged at a temperature of 90° C. for 1 hour were greater than 5%, and the shear strength (S 23 ) at 90°C (S 90 ) ratio (S 90 / S 23 ) was less than 0.25. This shows that the foam sheets of Comparative Examples 1 and 2 and the sheet of Comparative Example 3 are inferior in fixing performance at high temperatures.
Claims
1. At least one of the MD shrinkage rate and the TD shrinkage rate when aged at a temperature of 90° C. for 1 hour is 5% or less, Shear strength at 23°C (S 23 ) versus shear strength at 90°C (S 90 ) ratio (S 90 / S 23 ) is 0.25 or more, The flexural modulus is 160 kPa or less, The foam is obtained by foaming a resin composition including a resin (A) having a structural unit derived from propylene and a polyethylene-based resin (B), The polyolefin resin foam sheet, wherein the resin (A) contains a polypropylene resin, an ethylene-propylene random copolymer rubber, and an olefin thermoplastic elastomer.
2. The thickness is 1.5 mm or less, 2. The polyolefin resin foam sheet according to claim 1, having a 25% compressive strength of 600 kPa or less.
3. 3. The polyolefin resin foam sheet according to claim 1, which has a shear strength of 0.15 MPa or more at a temperature of 90°C.
4. The polyolefin resin foam sheet according to any one of claims 1 to 3, wherein at least one of an average cell diameter in MD and an average cell diameter in TD is 250 µm or less.
5. The polyolefin resin foam sheet according to any one of claims 1 to 4, having a degree of crosslinking of 30 to 80 mass%.
6. Apparent density: 0.06 to 0.7 g / cm 3 The polyolefin resin foam sheet according to any one of claims 1 to 5, which is
7. The polyolefin-based resin foam sheet according to any one of claims 1 to 6, wherein a total content of the polypropylene-based resin and the ethylene-propylene random copolymer rubber in the resin composition is 50 to 90 parts by mass per 100 parts by mass of a resin component of the resin composition.
8. The polyolefin resin foam sheet according to any one of claims 1 to 7, wherein the content of the olefin-based thermoplastic elastomer in the resin composition is 2 to 50 parts by mass per 100 parts by mass of a resin component of the resin composition.
9. 9. An adhesive tape comprising the polyolefin resin foam sheet according to claim 1 and an adhesive layer provided on at least one surface of the polyolefin resin foam sheet.
Citation Information
Patent Citations
Resin foam sheet, method for producing resin foam sheet, and adhesive tape
JP2018053224A
Polyolefin resin foam sheet and adhesive tape using the same
JP2019059819A
Polyolefin resin foam sheet and adhesive tape using the same
JP2019059932A
Double-sided adhesive tape
JP2019065153A